Sublimation Kinetic Studies of the Zr(tmhd)4 Complex - T. S. Arul Jeevan; K. S. Nagaraja (Journal of Chemistry)
The thermal behaviour of tetrakis(2,2,6,6-tetramethyl-3,5-heptanedionato)zirconium(IV), [Zr(tmhd)4] was investigated by nonisothermal and isothermal thermogravimetric methods in a high pure nitrogen atmosphere. The influence of the heating rate in dynamic measurements (6, 8, 10, and 12°C/min) on activation energy was also studied. The nonisothermal sublimation activation energy values determined following the procedures of Arrhenius, Coats and Redfern, Kissinger, and Flynn-Wall yielded 76±5, 92±2, 81±8, and 72±7 kJ/mol, respectively, and the isothermal sublimation activation energy was found to be 87±4 kJ/mol over the temperature range of 411–462 K. Different reaction mechanisms were used to compare with this value. Analysis of the experimental results suggested that the actual reaction mechanism was an Rn deceleration type.